An Investigation of the Effects of Specimen Gripping Systems on Shear Stress at the Geosynthetic/Geosynthetic Interface in Landfill Applications - Sikwanda, Charles (Department of Civil Engineering, 2020)
The use of geosynthetics has rapidly increased in nearly all geotechnical related fields as they allow for innovations, improved performance and cost effectiveness in projects. However, when geosynthetics are installed on sites, particularly on landfill slopes, their interface interaction against the adjacent materials becomes the critical section where shear failure is likely to occur. For this reason, their shear strength behaviour is determined in the laboratory at anticipated site conditions, mainly using a direct shear device to obtain design parameters. These laboratory tests are preferably conducted in accordance with ASTM-D5321 and ASTM-D6243 standards. The direct shear equipment, however, requires the use of an appropriate gripping system for shear to take place in the desired interface. Otherwise, tensile failure within the tested geosynthetics will be generated, resulting in obtaining design parameters which do not represent the actual field performance of the tested geosynthetics. This could lead to unsafe, cost ineffective, etc. design of projects with the respective geosynthetic materials. To date, many laboratories use a variety of gripping systems in a direct shear device to determine the shear design characteristics of geosynthetics and the preferred system remains a topic of concern. As a consequence, there is a large variability in the test results obtained, thus, difficulties in their interpretations. In this research, the effects of two commonly used gripping systems in a direct shear device, namely the nail plate (NP) and sandpaper (SP), have been investigated using a landfill case liner. This liner consisted of the three different classes of geosynthetics which are popularly installed in a landfill i.e. geotextile, geomembrane and geosynthetic clay liner. The results revealed that there exists a dissimilarity in the mobilized shear strength at geosynthetic interface when the NP is used as compared to the utilization of the SP due to the specimen engagement with the respective gripping systems. The exact difference, however, was not established as it varied depending on the interface tested. This highlighted the need to standardize the geosynthetic gripping systems in a direct shear device as it would capture these variations, increase result reproducibility and ease their interpretations.